PSYCHOLOGICAL DISTRESS AMONG UNDERGRADUATE MEDICAL STUDENTS OF PESHAWAR, PAKISTAN - Ali, Muhammad; Sethi, Mifrah Rauf; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2018)
Objective: To find out the level of psychological distress among medical stu- dents of Peshawar. Methodology: This cross-sectional study included undergraduate medical stu- dents of Peshawar, Pakistan. Kessler psychological distress scale (K10) ques- tionnaire was used to assess the level of psychological distress in students. The questionnaire consisted of 10 questions with five response options i.e., none of the time (1) to all of the time (5). The scores between 10 to 19 indicates a person to be well, 20-24 indicates that there is likelihood of having mild psychological distress, 25-29 for having moderate and 30-50 for having severe psychological distress. Data analysis was carried out using SPSS v.20 and a p value of <0.05 was considered significant when tests of significance were applied. Results: The mean age of the sample (n=1284) was 20.7 +1.6 years with major- ity of female students (n=714, 55.6%). The response rate was 92%. The Cron- bach's alpha reliability of K10 in our study was 0.839. The results showed that 281 (21.9%), 341 (26.6%) and 319 (24.8%) students had mild, moderate and se- vere psychological distress, respectively. Females had significantly higher levels of psychological distress as compared to male students (p =0.000). There was no significant difference in the level of psychological distress in the students of private and public sector medical colleges (p =0.320). Conclusion: Three out of every four students are experiencing psychological distress which need to be addressed to help them improve their efficiency in academics and to enhance their overall psychological and physical health.